Isothermal Oxidation Behavior of Gadolinium Zirconate (Gd2Zr2O7) Thermal Barrier Coatings (TBCs) produced by Electron Beam Physical Vapor Deposition (EB-PVD) technique - Doleker Kadir Mert (Open Chemistry, 2018)
Thermal Barrier Coatings (TBCs) provide thermal insulation for gas turbine components operating at high temperatures. Generally, TBCs were produced on a MCrAlY bond coat with 7-8% Yttria Stabilized Zirconia (YSZ) using Atmospheric Plasma Spray (APS) technique. In this study, Inconel 718 substrate material was coated with CoNiCrAlY bond coat using high velocity oxygen fuel (HVOF) technique. Afterward, Gd2Zr2O7 was deposited on samples using Electron Beam Physical Vapor Deposition (EB-PVD) technique. Produced TBCs were exposed to isothermal oxidation tests at 1000°C for 8 h, 24 h, 50 h and 100 h in muffle furnace. Scanning electron microscopy-energy distribution X-ray (SEM-EDX) spectroscopy was used to investigate thermally grown oxide (TGO) layer and TGO growth behavior of TBCs. In addition, X-ray Diffractometer (XRD) analysis was performed to TBCs to understand whether phase transformation occurs or not before and after oxidation.